Mechanistic study of transesterification in TBD-catalyzed ring-opening polymerization of methyl ethylene phosphate. (September 2019) - Nifant'ev, Ilya E.; Shlyakhtin, Andrey V.; Tavtorkin, Alexander N.; Kosarev, Maxim A.; Gavrilov, Dmitry E.; Komarov, Pavel D.; Ilyin, Sergey O.; Karchevsky, Stanislav G.; Ivchenko, Pavel V.
Graphical abstract: Highlights: DFT modeling of TBD-catalyzed ROP of methyl ethylene phosphate. The calculated difference in ΔG ≠ of ROP and transesterification is 10–13 kcal/mol. Trimethyl phosphate suppress transesterification. Effective synthesis of linear poly(methyl ethylene phosphate) with narrow MWD. Abstract: It is well known that ring-opening polymerization (ROP) of sterically unhindered cyclic ethylene phosphates, initiated by both organocatalysts and coordination catalysts, is accompanied by transesterification (TE) even at subzero temperatures. To clarify this phenomenon from the mechanistic point of view, we calculated (DFT, B3PW91/DGTZVP) the reaction profiles of the ROP for 2-methoxy-1, 3, 2-dioxaphospholane-2-oxide (methyl ethylene phosphate, MeOEP) and of the transesterification processes for poly(MeOEP) and trimethyl phosphate (TMP) in the presence of 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) organocatalyst. We found that the free activation energy of TE is substantially higher (10–13 kcal/mol) than the ROP activation barrier. To verify the calculation results, we investigated the chemical behavior of low molecular weight trimethyl phosphate (TMP) in the TBD-catalyzed polymerization of MeOEP. We demonstrated that TMP was not affected by transesterification, which correlates with the calculation results. However, we found that the polymerization of MeOEP in the presence of TMP leads to the formation of linear poly(MeOEP) with given Pn and narrow MWD even at >99% monomer conversion degree. A similar pattern was revealed for the synthesis of poly(MeOEP) with the coordination catalyst of aryloxy-alkoxy magnesium complex [(BHT)Mg(μ-OBn)(THF)]2 (BHT = 2, 6-di- tert -butyl-4-methylphenoxy). To explain the difference in the chemical behavior of TMP and polyphosphate, we assumed that poly(MeOEP) in the solution represents a dense globule, which leads to a decrease in the entropy of transesterification. To confirm this assumption, we studied the solution behavior of poly(MeOEP) in CHCl3 and in TMP. Both CHCl3 and TMP were found to be poor solvents for poly(MeOEP) in terms of KMH solution theory (α = 0.53 and 0.33, respectively). We assume that it is the conformation of the polymer in the solution that determines the tendency of the polyphosphate towards transesterification.